The informational life of the poor: A study of digital access in three Mexican towns - Judith Mariscal Avilés; Sebastián Benítez Larghi; María Angélica Martínez Aguayo (International Telecommunications Society (ITS), 2015)
This paper seeks to contribute to the debate on the impact of the adoption of information technologies (ICT) in poverty reduction by understanding how the poor obtain, share and use ICT on their everyday life - what we call the informational lives of the poor. It identifies the opportunities and challenges regarding ICT adoption in three rural communities with different levels of marginalization and connectivity in Mexico. Using "before and after" studies we attempt to identify and understand mechanisms through which ICT (and broadband, in particular), may have an impact on poverty alleviation. Using a combination of the Capabilities Approach and Livelihoods Perspective, this research shows that mobile broadband access (as opposed to fixed shared access) and effective training through the role of infomediaries enables low-income communities to develop new skills, to engage in new practices and to find useful applications for old and new abilities, needs and interests. A specific finding that has not received attention in the literature is the productive role of immediate family members as infomediaries; the weight of family networks plays a crucial role in learning about ICTs. These networks fuel a sense of confidence required to handle knowledge and practices that are initially alien in this sector. We found that ICT adoption changes the pattern of information seeking and enhances informational capabilities and existing assets of low-income communities. Through our control case, that did not have any connectivity, we identified the high transaction cost people face as well as the business opportunities the digitally excluded forego.
Keywords: 330